PENGARUH CAR, LDR DAN NPL TERHADAP ROA PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - barasa, yulan rahayu; S.E.,M.Si, Hikmah (LPPM Universitas Putera Batam, 2021)
This study was conducted with the aim of understanding empirically about the influence of Capital Adequacy Ratio (CAR), Loan Deposit Ratio (LDR), and Non Performing Loan (NPL) partially on Return On Assets (ROA) of private foreign exchange banks listed on the Indonesian Stock Exchange. In addition, this study also empirically examines the effects of CAR, LDR and NPL on ROA simultaneously in private foreign exchange banks listed on the Indonesian Stock Exchange. This study uses a quantitative research method with a causal type of research. The population of the treatise written 30 people and 27 people with a sample period of 5 years of studies since 2016 - 2020. The sample selection using purposive sampling method. The data analysis method used in this study was multiple linear regression analysis, statistical tests included t test for partial test and F test for simultaneous test. Prior to statistical tests, the classical assumption tests performed were normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. The results of t test showed that CAR had a negative effect on ROA. LDR had a positive but insignificant effect on ROA. And NPLs have a negative and significant impact on ROA